Panorama de las PyME del sector turístico en Colombia en el marco de la Alianza del Pacífico (2017)
The paper presents a perspective of SMEs in the tourism sector in Colombia as part of the Pacific Alliance (AP) from the analysis and diagnosis of the competitiveness of Colombian SMEs. For this, the respective study is done based on statistical data provided by different entities, from which an overview of the situation of SMEs in the tourism sector of Colombia against sectoral dynamics in Mexico, Peru and Chile runs. We analyze which activities register a greater contribution to the sector, the main nationalities of tourists entering each country, among other things. Finally, a stocktaking of the Colombian tourism sector is made as to the other countries in question, thereby evaluating weaknesses and strengths that has the sector of the national economy.